Exploring the false promise of entrepreneurship through a postfeminist critique of the enterprise policy discourse in Sweden and the UK. (January 2021) - Ahl, Helene; Marlow, Susan
Contemporary theories of neoliberalism and entrepreneurship are entwined; both hinge upon the use of agency within free markets to realise individual potential, enhance status and attain material rewards. Postfeminism, as a discrete but related discourse, suggests this context is conducive to encouraging women to draw upon their agency, skills and personal profile to enhance achievements and returns. We draw from these related, but discrete discourses, when critically analysing how postfeminist assumptions shape Swedish and UK government policies aimed at expanding women's entrepreneurship. Despite differing historical antecedents regarding state engagement with equality and welfare regimes, we illustrate how postfeminist assumptions have infiltrated policy initiatives in both cases. This infiltration has, we suggest, suppressed criticisms that in a context of persistent structural discrimination, lack of welfare benefits and contrived aspirational role models, entrepreneurship constitutes a poor career choice for many women. Consequently, we challenge the value of contemporary policy initiatives encouraging more women to enter entrepreneurship.